Proceedings of the 2014 Conference on Innovation &Amp; Technology in Computer Science Education - ITiCSE '14 2014
DOI: 10.1145/2591708.2602671
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reward structures in an inverted course

Abstract: The inverted or flipped classroom [4] has been shown to be effective in computer science [5, 2, 1]. Inverted teaching depends on students engaging in both pre-and in-lecture activities. What reward structure will motivate students to do so? We report on our experience with inverted teaching for a one-month unit in a third-year database course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…On the contrary, other studies did not report any learning difference between both methodologies in a variety of courses: Computer Architecture [12], CS1 [41], CS1 with Scala [38] and CS1 with Python [26]. Students' satisfaction has been also studied in many publications, some studies detected improvements (in favor of FC) in different courses: Computer Programming in Meteorology [17], Computer Systems [16] and Databases [46]. In the later study, students from the FC group commented on the increase of their workload.…”
Section: The Use Of Flipped Classroom In Computer Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, other studies did not report any learning difference between both methodologies in a variety of courses: Computer Architecture [12], CS1 [41], CS1 with Scala [38] and CS1 with Python [26]. Students' satisfaction has been also studied in many publications, some studies detected improvements (in favor of FC) in different courses: Computer Programming in Meteorology [17], Computer Systems [16] and Databases [46]. In the later study, students from the FC group commented on the increase of their workload.…”
Section: The Use Of Flipped Classroom In Computer Sciencementioning
confidence: 99%
“…Finally, while most of the works mentioned within the scope of CS study full applications of the FC methodology, this work considers a partial application of it. The studies that observed positive results, either in learning outcomes [7], [14], [43], [45] or student's satisfaction [17], [46], mostly seem to deploy the FC approach on practical contents. Only Horton & Campbell's study [46] specifically focuses on an introductory topic about databases.…”
Section: A Increasing the Body Of Experiments About The Use Of Flippmentioning
confidence: 99%
“…Several studies have examined the benefits of flipped classroom in higher STEM and computer science education, and reported that the format had a positive impact on student outcomes and syllabus design [9,10,11].…”
Section: Related Workmentioning
confidence: 99%
“…Giannakos et al's [12] lists low-stakes quizzes outside and inside the classroom among successfully employed strategies. Horton et al [11] emphasize the effectiveness of low-stakes prep exercises with a "small-grade reward" leading to higher participation.…”
Section: Related Workmentioning
confidence: 99%
“…A study by Horton et al [9] reported that while exam performance increased with flipped classroom, student enjoyment was unaffected. Another study [10] associates performance with grade-based incentives, with variable results when grade incentives are removed. Köppe et al [11] document some common non-grade-related patterns that have proven effective in flipped classrooms.…”
Section: Related Workmentioning
confidence: 99%